Epidemiological and Molecular Characterization of Clostridioides difficile Infection in Canadian Outpatient Settings, 2015–2019. (October 2020) - PHAC, CNISP; Silva, Anada; Thampi, Nisha; Choi, Kelly Baekyung; Pelude, Linda; Frenette, Charles; Chow, Blanda; Control,; Lee, Bonita; Hospital, s; Taylor, Geoffrey; Hota, Susy; et al.
Abstract : Background: Healthcare services are increasingly shifting from inpatient to outpatient settings. Outpatient settings such as emergency departments (EDs), oncology clinics, dialysis clinics, and day surgery often involve invasive procedures with the risk of acquiring healthcare-associated infections (HAIs). As a leading cause of HAI, Clostridioides difficile infection (CDI) in outpatient settings has not been sufficiently described in Canada. The Canadian Nosocomial Infection Surveillance Program (CNISP) aims to describe the epidemiology, molecular characterization, and antimicrobial susceptibility of outpatient CDI across Canada. Methods: Epidemiologic data were collected from patients diagnosed with CDI from a network of 47 adult and pediatric CNISP hospitals. Patients presenting to an outpatient setting such as the ED or outpatient clinics were considered as outpatient CDI. Cases were considered HAIs if the patient had had a healthcare intervention within the previous 4 weeks, and they were considered community-associated if there was no history of hospitalization within the previous 12 weeks. Clostridioides difficile isolates were submitted to the National Microbiology Laboratory for testing during an annual 2-month targeted surveillance period. National and regional rates of CDI were stratified by outpatient location. Results: Between January 1, 2015, and June 30, 2019, 2, 691 cases of outpatient-CDI were reported, and 348 isolates were available for testing. Most cases (1, 475 of 2, 691, 54.8%) were identified in outpatient clinics, and 72.8% (1, 960 of 2, 691) were classified as community associated. CDI cases per 100, 000 ED visits were highest in 2015, at 10.3, and decreased to 8.1 in 2018. Rates from outpatient clinics decreased from 3.5 in 2016 to 2.7 in 2018 (Fig. 1). Regionally, CDI rates in the ED declined in Central Canada and increased in the West after 2016. Rates in outpatient clinics were >2 times higher in the West compared to other regions. RT027 associated with NAP1 was most common among ED patients (26 of 195, 13.3%), whereas RT106 associated with NAP11 was predominant in outpatient clinics (22 of 189, 11.6%). Overall, 10.4% of isolates were resistant to moxifloxacin, 0.5% were resistant to rifampin, and 24.2% were resistant to clindamycin. No resistance was observed for metronidazole, vancomycin, or tigecycline. Compared to CNISP inpatient CDI data, outpatients with CDI were younger (51.8 ± 23.3 vs 64.2 ± 21.6; P < .001), included more females (56.4% vs 50.9%; P < .001), and were more often treated with metronidazole (63.0% vs 56.1%; P < .001). Conclusions: For the first time, CDI cases identified in outpatient settings were characterized in a Canadian context. Outpatient CDI rates are decreasing overall, but they vary by region. Predominant ribotypes vary based on outpatient location. Outpatients with CDI are younger and are more likely female than inpatients with CDI. Funding: None Disclosures: Susy Hota reports contract research for Finch Therapeutics.